Analyzing product greening spillovers in multi-product markets. (February 2022) - Awasthy, Prakash; Gouda, Sirish; Ghosh, Debabrata; Swami, Sanjeev
Abstract: Documented cases of sustainable initiatives of firms show that green efforts in one market often have spillover effects on other markets. The critical question is, how do firms harness and respond to such market spillovers. To answer this, the paper examines two settings where, a firm operates in two different markets with spillovers and secondly, where it faces marketplace competition. Spillovers can be positive or negative. Using an analytical approach, the paper examines pricing and greening strategies of a firm in these scenarios, conducts market comparisons, and examines specific conditions where the firm may not invest in greening. The findings show that under the threat of spillovers from competitor's green efforts, a focal firm increases its greening efforts and prices. Further, the absence of consumer green sensitivity in the primary market does not deter a firm from greening, if spillovers exist. Under negative spillovers, a firm can still invest in positive green efforts if the negative spillover effect is below a threshold. However, under competitive threat, a firm may lose competitive advantage as its competitor (with positive green spillovers), increases its greening efforts to compete in both the markets. Highlights: We analyze firms' decisions under positive and negative market spillovers. Environmental awareness' absence is not a deterrent for greening under spillovers. Firm can put positive green efforts if the negative spillover is below a threshold. Facing competitor's spillover threat, a firm increases its own green efforts and prices.